IMPLEMENTASI PENYELESAIAN SENGKETA PERDAGANGAN INTERNASIONAL DALAM WORLD TRADE ORGANIZATION (WTO) BAGI NEGARA BERKEMBANG - Heppy Koespitasari, Ara (Katalogis, 2015)
Dispute settlement system of WTO is a main element assuring the security and the certainty against multilateral trade. The forming is dispute settlement system is more oriented to law will create a situation that emphasizing the equal treatment on rights and duties toward the nation members. The dispute settlement mechanism of WTO function effectivelly. The implementation is conducted by a body called Dispute Settlement Body. Therefore, the trade dispute settlement in WTO, the developing countries get a special and differential treatment particulary when the dispute involving the developed countries. The giving of special and differential treatment is a step that may help the developing countries to be in balance position of the dispute that involving the developed countries.